ASHA-Life Intervention Perspectives Voiced by Rural Indian Women Living With AIDS. Issue 4 (2nd April 2016) - Nyamathi, Adeline; Ekstrand, Maria; Srivastava, Neha; Carpenter, Catherine L.; Salem, Benissa E.; Al-Harrasi, Shawana; Ramakrishnan, Padma; Sinha, Sanjeev
Abstract : In this focus group study, we explored the experiences of 16 rural women living with AIDS (WLA) who participated in the Asha-Life (AL) intervention to gain an understanding of the environmental, psychosocial, and cultural impact of the AL on their lives. Four themes emerged among AL participants: (a) the importance of tangible support, (b) need for social support, (c) ongoing challenges to accessing antiretroviral therapy (ART), and (d) perspectives on future programs. Our research findings support the development of future programs targeting mother–child dyads which emphasize nutritional knowledge, while reducing barriers to receiving ART, and physical, emotional, and financial support.